2011
DOI: 10.1002/jgm.1583
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic control elements promote long‐term expression of human coagulation factor IX gene in hydrodynamically transfected mice

Abstract: We have shown in mouse models that hydrodynamic transfection of pBS-HCRII-HP-FIXA and pBS-HCRI/II-HP-FIXA was able to induce and maintain the expression and clotting activity of human factor IX for a long period of time at a potentially therapeutic level. With an appropriate delivery system, this type of plasmid vector could be clinically useful for the hepatic expression of therapeutic genes including human factor IX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…They reported therapeutic plasma levels of protein over six months and functional activity in the correction of bleeding after tail clipping. Likewise, in 2011, Kim et al [ 34 ] reported long-term expression of hFIX (above 500 ng/mL) and clotting activity for seven months in FIX knockout mice after hydrodynamic injection without genome integration. Given the positive outcomes obtained, researchers evaluated gene constructions with greater potential to be employed in humans.…”
Section: Gene Transfer Applicationsmentioning
confidence: 99%
“…They reported therapeutic plasma levels of protein over six months and functional activity in the correction of bleeding after tail clipping. Likewise, in 2011, Kim et al [ 34 ] reported long-term expression of hFIX (above 500 ng/mL) and clotting activity for seven months in FIX knockout mice after hydrodynamic injection without genome integration. Given the positive outcomes obtained, researchers evaluated gene constructions with greater potential to be employed in humans.…”
Section: Gene Transfer Applicationsmentioning
confidence: 99%
“…transfer of the FIX gene in vivo is possible even by the naked plasmid DnA, as has been shown in animal models. Hydrodynamic injection of expression plasmid containing human FIX cDnA and the hepatic control region was sufficient to achieve therapeutic levels of FIX in deficient mice for 210 days [75]. the delivery technique employed -injection of 50 µg of the plasmid in 2 ml of solution in 5-8 sec into the tail vein -is definitely unsuitable for human therapy, and a significant modification of hydrodynamic injection should be invented before clinical studies can take place.…”
Section: Gene Therapy Of Hemophilia Bmentioning
confidence: 99%
“…Hydrodynamic injection of expression plasmid containing human FIX cDNA and the hepatic control region was sufficient to achieve therapeutic levels of FIX in deficient mice for 210 days [75]. The delivery technique employed – injection of 50 µg of the plasmid in 2 ml of solution in 5-8 sec into the tail vein – is definitely unsuitable for human therapy, and a significant modification of hydrodynamic injection should be invented before clinical studies can take place.…”
Section: Gene Therapy Of Hemophilia Bmentioning
confidence: 99%